2018
DOI: 10.1002/dys.1593
|View full text |Cite
|
Sign up to set email alerts
|

What is dyslexia? An exploration of the relationship between teachers' understandings of dyslexia and their training experiences

Abstract: Given that an estimated 5–10% of the worldwide population is said to have dyslexia, it is of great importance that teachers have an accurate understanding of what dyslexia is and how it effects their students. Using results from a large‐scale survey of teachers in England and in Wales (N ≈ 2,600), this paper demonstrates that teachers held a basic understanding of dyslexia, based on the behavioural issues that it is associated with. Teachers lacked the knowledge of the biological (i.e., neurological) and cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 25 publications
5
60
0
5
Order By: Relevance
“…For the second question, teachers' familiarity significantly correlated with their teaching practices of dyslexia associated with poor working memory, which many previous studies similarly proved. This finding was comparable to Knight (2018), who assumed that when teachers have competent knowledge of dyslexia, they may show competent practices of dyslexia. Therefore, "poor knowledge of dyslexia leads to poor practice" (Knight, 2018, p.217).…”
Section: Discussionsupporting
confidence: 80%
“…For the second question, teachers' familiarity significantly correlated with their teaching practices of dyslexia associated with poor working memory, which many previous studies similarly proved. This finding was comparable to Knight (2018), who assumed that when teachers have competent knowledge of dyslexia, they may show competent practices of dyslexia. Therefore, "poor knowledge of dyslexia leads to poor practice" (Knight, 2018, p.217).…”
Section: Discussionsupporting
confidence: 80%
“…However, the detail as to how this should be undertaken has not been given. In fact, research has shown that the enactment of this legislation and guidelines has been unsuccessful in ensuring the active and meaningful participation of parents/carers in discussions about provision for their children [16,[33][34]. This is indicative of a system that is not fulfilling its brief.…”
Section: Roles and Values In Educationmentioning
confidence: 99%
“…Large-scale research by Knight (2018) involving 2,600 participants, found that teachers lacked understanding of dyslexia in two main areas: biological (neurological) and cognitive (processing).…”
Section: Discussionmentioning
confidence: 99%
“…Although dyslexia can affect individuals differently, it can include one's difficulty in: organisation, literacy, memory, concentration, time keeping and spelling. Dyslexia can be defined in different ways and have different effects for individual students but rates of dyslexia within the population are reported to be up to 20% (Knight, 2018).…”
Section: Introductionmentioning
confidence: 99%